2016
DOI: 10.1177/2158244016666605
|View full text |Cite
|
Sign up to set email alerts
|

Black Adolescent Females’ Perceptions of Racial Discrimination When Accessing Reproductive and General Health Care

Abstract: The Institute of Medicine defines health disparities as "racial or ethnic differences in the quality of health care that are not due to access-related factors or clinical needs, preferences, and appropriateness of intervention" (Smedley, Stith, & Nelson, 2003). In this case, discrimination at the individual patient-provider level is thought to manifest as differences in care resulting from biases, prejudices, and stereotyping in clinical communication and decision making. There is evidence that patients who pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…In some cases, racism was explored in relation to other forms of oppression. For example, 4 articles explored sexism, 50,57,58,61 2 articles examined classism, 50,61 and one article addressed colorism. 57…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In some cases, racism was explored in relation to other forms of oppression. For example, 4 articles explored sexism, 50,57,58,61 2 articles examined classism, 50,61 and one article addressed colorism. 57…”
Section: Resultsmentioning
confidence: 99%
“…Racism was most commonly examined in general health care such as check-up visits with general practitioners ( n = 5; 38%) 20,53,6062 including both general mental health care 52 and psychiatric counseling and care 54,56,58,62 (see Table 2). Racism was explored in a variety of other health care settings but with less frequency, including reproductive health, 50,57 autism diagnosis and care, 51 vaccine access and uptake, 53 medical research on vaccines, 53 pediatrician services, 55 and school health services. 62 Across these health care contexts, interpersonal racism between health practitioners and youth was most explored.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have also shown that contextual factors, such as levels of historical knowledge of racism, previous past experiences of racism, and diversity policies, shape individuals' perceptions of racism [56][57][58][59]. For example, Blacks tend to compare racial progress to ideal standards of equality, while Whites tend to compare racial progress to the past, considering how much things have improved.…”
Section: Introductionmentioning
confidence: 99%